Short Term Postoperative Outcomes of Colostomy Closure - Pažusis, Matas; Maželytė, Rūta; Buzaitė, Kristina; Saladžinskas, Žilvinas (Lietuvos chirurgija, 2019)
Introduction. Colostomies are most often formed for patients diagnosed with colorectal malignancies. If colostomy is not permanent it could be closed after a certain period of time. Postoperative complications may include anastomotic leakage, ileus and wound infection. Purpose. To review the outcomes of colostomy closure during a short term follow-up period. Methods. A retrospective analysis of data form patients who underwent a colostomy closure surgery at the Section of the Surgery Department LSMU KK between 2012 through 2017 was carried out. The variables analysed were: age, characteristics of complications, number of hospitalisation days, reasons why the colostomy was formed, whether neoadjuvant treatment was given, timing before colostomy closure, whether resection was performed, type of resection, type of anastomosis, duration of surgery and characteristics of post operative period. Statistical data was analysed using Microsoft Excel program. Results. Medical records of 88 patients were analysed. The mean age of the patients was 56±1.6 (from 22 to 84). Surgeries performed because of the following reasons: sigmoid bowel cancer – 35 (39.8%), colon cancer – 11 (12.5%), large intestine diverticulosis – 20 (22.7%), abdominal trauma following car accident – 13 (14.8%), iatrogenic sigmoid bowel perforation after colonoscopy – 4 (4.6%), Crohn’s disease – 1 (1.1%), paraproctitis and ischiorectal abscess – 2 (2.3%), ischaemic colitis – 1 (1.1%), megacolon – 1 (1.1%). Colostomies were closed in average after 10.13±2.14 months. Segmental resection was performed for 31 (36.5%) and marginal resection for 54 (63.5%) patients. The mean duration of colostomy closure surgery was 154.56±6.48 min. The mean duration of hospitalization was 9.43±0.62 days. 69 (78.1%) patients experienced a good postoperative recovery. The mean length of hospitalisation for these patients was 7.78±2.42 days. 19 patients (21.9%) experienced post operative complications, which is why their mean length of hospitalization was 15.05±9.58. Post operative complications were: irregular heartbeat 4 (4.5%), seroma and hematoma 5 (5.7%), ileus 1 (1.1%), nausea 1 (1.1%), intestinal bleeding 1 (1.1%), anastomotic leakage 1 (1.1%), abdominal pain 1 (1.1%), fever 4 (4.5%), vesicorectal fistula formation 1 (1.1%). 2 (2.3%) reoperations were performed. One relaparotomy was performed due to anastomotic leakage and one due to ileus. No deaths were recorded. Conclusions. 1. Colostomies were closed in average after 10.13±2.14 months. 2. After colostomy closure 69 (78.1%) patients experienced a post operative recovery without complications. 3. Complications that most often occurred during post operative period were: fever 4 (4.5%), irregular heartbeat 4 (4.5%), seroma and hematoma 5 (5.7%).